Optimizing zakāt management as an effort to alleviate poverty: a case study at the Central Java Baznas - Faizah, Fita Nurotul (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2022)
Apart from being a religious obligation, economically , zakāt can play a role inalleviating poverty. This study aims to determine the extent to which themanagement of zakāt, infāq, and ṣadaqah in Central Java Baznas is an effort toalleviate poverty. This research uses a descriptive qualitative method with a casestudy approach. The data was obtained through observation and documentation,which includes the management and distribution of zakāt, infāq, and ṣadaqah,and mustaḥik zakāt at Baznas Central Java. The study results prove that thecollection of zakat, infāq, and ṣadaqah at Baznas Central Java can effectivelybecome a potential source of funds for poverty alleviation and improving thequality of human resources according to the consumptive and productive zakātutilization model. This research can be used for consideration, evaluation, andalternative strategies for managing zakat, infāq and ṣadaqah at Baznas in CentralJava, particularly in zakāt management institutions.Keywords: zakāt; infāq; ṣadaqah; poverty; Baznas, Central Java.